Skeletal muscle fatigue and decreased efficiency: Two sides of the same coin? - Grassi, B.; Rossiter, H. B.; Zoladz, J. A. (Exercise and Sport Sciences Reviews, 2015)
During high-intensity submaximal exercise, muscle fatigue and decreased efficiency are intertwined closely, and each contributes to exercise intolerance. Fatigue and muscle inefficiency share common mechanisms, for example, decreased "metabolic stability," muscle metabolite accumulation, decreased free energy of adenosine triphosphate breakdown, limited O2 or substrate availability, increased glycolysis, pH disturbance, increased muscle temperature, reactive oxygen species production, and altered motor unit recruitment patterns.